APPROACH TO ADAPTIVE LEARNING MANAGEMENT SYSTEM DESIGN - Vitaly A. Gaevoy; Dmitry Yu. Zakharov (Открытое образование (Москва))
In this paper, we describe how to increase the learning management systems effi ciency by using an adaptive approach. In our work we try and summarize the existing systems; the adaptability absence problem is discovered, programming and architectural adaptive learning management system designing approach is offered.